Gaullism and Atlanticism are Main Foreign Policy Paradigms of the Fifth Republic - D. Y. Mikhailov (Vestnik MGIMO-Universiteta)
Gaullism and Atlanticism in the foreign policy of the Fifth Republic appear as two fundamental but mutually exclusive ideological paradigms that, in various combinations, traditionally determined Paris’s behavior on the international stage. A comparative analysis of the ideological constructions of Gaullism and Atlanticism shows the fundamental reason for the conceptual discrepancy between the two doctrines. Gaullism calls on France to preserve its status as a world power at any cost. Atlanticism serves the geostrategic purpose of maintaining American military and political control over Europe. For this reason, Atlanticism does not recognize any other world powers within the Western universe but the United States.A retrospective view of the Gaullist and Atlanticist interaction reveals a steady trend towards a gradual shift of the Fifth Republic from Charles de Gaulle’s diplomacy principles. This trend led to the beginning in 2007 of a new era of the absolute dominance of Atlanticism in French foreign policy compared with the post-war period of the Fourth Republic.The advent of this era was marked by a significant improvement in France’s relations with the United States and NATO and increasing French activism on the track of Euro-federalist integra-tion, but, in general, by the perceptible banalization of France’s voice in international affairs.The results of this study help build future relations between Russia and France.